2019
DOI: 10.1101/833343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A reservoir of rituximab-resistant splenic memory B cells contributes to relapses after B-cell depletion therapy

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disease mediated by pathogenic antibodies directed against platelet antigens, including GPIIbIIIa. Taking advantage of spleen samples obtained from ITP patients, we characterized by multiples approaches the onset of disease relapses occurring after an initial complete response to rituximab. Analysis of splenic B cell immunoglobulin heavy chain gene repertoire at bulk level and from single anti-GPIIbIIIa B cells revealed that germinal centers were fueled by B cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…Single cell culture was performed as previously described (Crickx et al, 2019). Single B cells were sorted in 96-well plates containing MS40 cells expressing CD40L (kind gift from G. Kelsoe).…”
Section: Methods Detailsmentioning
confidence: 99%
“…Single cell culture was performed as previously described (Crickx et al, 2019). Single B cells were sorted in 96-well plates containing MS40 cells expressing CD40L (kind gift from G. Kelsoe).…”
Section: Methods Detailsmentioning
confidence: 99%
“…Single cell culture was performed as previously described (Crickx et al, 2019): single B cells were sorted in 96-well plates containing MS40 cells expressing CD40L (kind gift from G. Kelsoe). Cells were co-cultured at 37 C with 5% CO2 during 21 or 25 days in RPMI-1640 (Invitrogen) supplemented with 10% HyClone FBS (Thermo Scientific), 55 mM 2-mercaptoethanol, 10 mM HEPES, 1 mM sodium pyruvate, 100 units/mL penicillin, 100 mg/mL streptomycin, and MEM non-essential amino acids (all Invitrogen), with the addition of recombinant human BAFF (10 ng/mL), IL2 (50 ng/mL), IL4 (10 ng/mL), and IL21 (10 ng/mL; all Peprotech).…”
Section: Single-cell Culturementioning
confidence: 99%
“…All culture supernatants from single-cell cultured memory B cells used in this study were generated and reported as part as a previous study (see Sokal et al, 2021b). Briefly, single B cells were sorted in 96-well plates containing MS40L lo cells expressing CD40L (kind gift from G. Kelsoe, Crickx et al, 2021;Luo et al, 2009). Cells were co-cultured at 37 C with 5% CO2 during 21 or 25 days in RPMI-1640 (Invitrogen) supplemented with 10% HyClone FBS (Thermo Scientific), 55 mM 2-mercaptoethanol, 10 mM HEPES, 1 mM sodium pyruvate, 100 units/mL penicillin, 100 mg/mL streptomycin, and MEM non-essential amino acids (all Invitrogen), with the addition of recombinant human BAFF (10 ng/ml), IL2 (50 ng/ml), IL4 (10 ng/ml), and IL21 (10 ng/ml; all Peprotech).…”
Section: Single-cell Culturementioning
confidence: 99%